If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 2(y + -2) = 7y + -2(y + -10) Reorder the terms: 5y + 2(-2 + y) = 7y + -2(y + -10) 5y + (-2 * 2 + y * 2) = 7y + -2(y + -10) 5y + (-4 + 2y) = 7y + -2(y + -10) Reorder the terms: -4 + 5y + 2y = 7y + -2(y + -10) Combine like terms: 5y + 2y = 7y -4 + 7y = 7y + -2(y + -10) Reorder the terms: -4 + 7y = 7y + -2(-10 + y) -4 + 7y = 7y + (-10 * -2 + y * -2) -4 + 7y = 7y + (20 + -2y) Reorder the terms: -4 + 7y = 20 + 7y + -2y Combine like terms: 7y + -2y = 5y -4 + 7y = 20 + 5y Solving -4 + 7y = 20 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -4 + 7y + -5y = 20 + 5y + -5y Combine like terms: 7y + -5y = 2y -4 + 2y = 20 + 5y + -5y Combine like terms: 5y + -5y = 0 -4 + 2y = 20 + 0 -4 + 2y = 20 Add '4' to each side of the equation. -4 + 4 + 2y = 20 + 4 Combine like terms: -4 + 4 = 0 0 + 2y = 20 + 4 2y = 20 + 4 Combine like terms: 20 + 4 = 24 2y = 24 Divide each side by '2'. y = 12 Simplifying y = 12
| 17x=16x | | x/12=x/4-2 | | E=lR | | 44=-u+188 | | 18x+64=19x | | x/5=x/6-3 | | 0x^2-71x-9=0 | | 106=161-w | | 4x^2-13x+3x=0 | | (15/x)=((x^2)-7x+17) | | -v+111=202 | | 1/3+7/8+4/5 | | -x+279=208 | | 3x-6(x+1)=-3x+19 | | 21/5(-13/4p+5)=651/5 | | X(6x-3)=(6x+9)(x-8) | | -4(5y-7)-y=-2(y-5) | | x*y=630 | | x(2x+3)=4 | | 3(x-8)=9x | | 3x+9-2x=13 | | 4x^4-20x^2+16=0 | | 26x+12=5(5x+4) | | 10-(2*-4)+3x=16 | | (5u+3)(5-u)=0 | | 3x+9-2x=14 | | 2x-6x+9=x-6+15 | | (7x^2+5x)/(x^2+1)-5x/(x^2-6) | | 5w+2.7=12 | | 9x^2+169=0 | | 3x+9x-4=3(4x+9) | | -8=-(-6x-3) |